When markets collide : - El-Erian, Mohamed A. (McGraw-Hill, 2008)
When Markets Collide is a timely alert to the fundamental changes taking place in today's global economic and financial systems--and a call to action for investors who may fall victim to misinterpreting important signals. While some have tended to view asset class mispricings as mere “noise,” this compelling book shows why they are important signals of opportunities and risks that will shape the market for years to come. One of today's most respected names in finance, Mohamed El-Erian puts recent events in their proper context, giving you the tools that can help you interpret the markets, benefit from global economic change, and navigate the risks.